ANALISIS INVENTARISASI ASET MILIK PEMERINTAH DAERAH KABUPATEN ROTE NDAO TAHUN 2019 - Cicilia Apriliana Tungga (Universitas Nusa Cendana, 2020)
This research aims to analyze the level of the importance and the performance of the implementation of factors that determine the successful inventory of assets in Rote Ndao Regency. Importance Performance Analysis (IPA) is used as an analysis tool to process research data. The results showed that asset inventory has not been fully optimal. This can be seen from the results of data analysis that is unbalancing between interest and performance levels. There are 4 inventory factors that are priority to improve performance, namely: regional asset logging activities in Rote Ndao District Government, improvement of updated data base, implementation of regional asset census to get correct and accurate asset data, and information technology capabilities and completeness of infrastructure facilities in the office supported by HR capabilities Keywords: inventory of regional assets , local government, Importance Performance Analysis (IPA)